2022
DOI: 10.7150/thno.70588
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of organelle interactions in cellular senescence

Abstract: Organelles are tiny structures with specific functions in eukaryotic cells. Since they are covered with membranes, different organelles can perform biological processes that are incompatible. Organelles can also actively communicate with each other to maintain cellular homeostasis via the vesicular trafficking pathways and membrane contact sites (MCSs), which allow the exchange of metabolites and other information required for normal cellular physiology. An imbalance in organelle interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 212 publications
(428 reference statements)
1
11
0
Order By: Relevance
“…Organelles can actively communicate and cooperate with each other through vesicle trafficking pathways and membrane contact points (MCSs) to maintain cellular homeostasis, which facilitates the exchange of metabolites and other information required for normal cellular physiology ( 223 ). Imbalances in organelle interactions may lead to various pathological processes, such as imbalances in cellular energy metabolism ( 224 ). Recent studies have shown that mitochondria could interact with various organelles ( 225 ), which are essential for energy metabolism and cell survival, and increasing evidence shows that mitochondrial dysfunction in skeletal muscle and mitochondrial overactivation may induce IR ( 226 ).…”
Section: The Mechanism Of Irmentioning
confidence: 99%
“…Organelles can actively communicate and cooperate with each other through vesicle trafficking pathways and membrane contact points (MCSs) to maintain cellular homeostasis, which facilitates the exchange of metabolites and other information required for normal cellular physiology ( 223 ). Imbalances in organelle interactions may lead to various pathological processes, such as imbalances in cellular energy metabolism ( 224 ). Recent studies have shown that mitochondria could interact with various organelles ( 225 ), which are essential for energy metabolism and cell survival, and increasing evidence shows that mitochondrial dysfunction in skeletal muscle and mitochondrial overactivation may induce IR ( 226 ).…”
Section: The Mechanism Of Irmentioning
confidence: 99%
“…Mitochondrial quality control (MQC) is an elaborate mechanism to maintain homeostasis, ensuring the enough numbers of functional mitochondria ( Pickles et al, 2018 ; Huang et al, 2022b ). Involving mitochondrial biogenesis, dynamics, and mitophagy, mitochondrial homeostasis is intimately correlated with normal kidney function ( Rahman et al, 2022 ) ( Figure 1 ).…”
Section: Mitochondrial Dysfunctions In Kidney Diseasesmentioning
confidence: 99%
“…The impaired mitochondrial FAO leads to insufficient supply of ATP, but also results in lipotoxicity, which together contribute to renal fibrosis ( Lv et al, 2019 ; Miguel et al, 2021 ). In both AKI and CKD models, the FAO failure and the following lipid accumulation commonly occur in renal TECs ( Rong et al, 2021 ; Xu et al, 2022 ), which could further trigger the impairment of mitochondrial structure and function ( Huang et al, 2022b ).…”
Section: Mitochondrial Dysfunctions In Kidney Diseasesmentioning
confidence: 99%
“…As a pivotal route for cholesterol transportation, MCSs participate in aging modulation by altering protein homeostasis, mitochondrial quality control, and lipid homeostasis (J. Huang, Meng, et al, 2022), and disrupted MCSs have also been linked to age-related diseases like neurodegeneration and CVDs. For example, ER extensively forms the MCSs with mitochondria and participates in ROS production, lipid and Ca 2+ flux, and autophagy, as well the pathogenesis of Alzheimer's disease, Parkinson's disease, amyotrophic lateral sclerosis, and other neurodegenerative diseases (Janikiewicz et al, 2018).…”
Section: Cellular Organelles and Vascular Agingmentioning
confidence: 99%